The Criminal Law of Forced Marriage on Children as a Preventive Measure on Sadz Dzariah's Perspective: Hukuman Pidana atas Perkawinan Paksa Terhadap Anak sebagai Tindakan Pencegahan dalam Perspektif Sadz Dzariah - Shodiq, Ja’far; Faizah, Isniyatin; Aqil Musthofa, Moh.; Mahdiyah, Aisyah Nur (Al-Jinayah : Jurnal Hukum Pidana Islam, 2024)
This research aims to find out the law that can criminally prosecute perpetrators of forced marriage on children and what is Sadz Dzariah's theoretical perspective on punishing perpetrators of forced marriage on children considering that marriage hurts children so the government makes criminal regulations, for cases of sexual violence where children become victims. This is most important because every child has the right to survival, growth, and development and the right to protection from violence and discrimination. In this research, the author uses a juridical-normative research method that combines conceptual analysis with legislation. The result is that, first; To provide protection and guarantee the rights of children, the government has established various laws and regulations that can prosecute perpetrators of forced marriage and sexual violence against children, such as; the Law Number 35/2014article 76 D, Law number 17/2016 article 81 and Law number 12/2022 article 10. Second; The existence of criminal articles for perpetrators of forced marriage is an effort by the government to close (سد) so that child marriage does not occur which becomes a way or cause (الذريعة) the emergence of negative impacts on children.